The Effectiveness of Feeding Azolla Microphylla on Catfish (Clarias Batrachus) Growth - Noviyanti, Anita; Husna, Fauzul; Ridhwan, Muhammad; Surya, Erdi; Armi, Armi; Masyudi, Masyudi; Walil, Kamalliansyah (International Conference on Multidisciplinary Research, 2020)
The usage of Azolla Microphylla as fish feed provides several advantages for fish farmers such as; the low-cost, the easy-to-obtain, and the taste that is favoured by some freshwaterfish especially catfish (Clarias Batrachus). Azolla Microphylla is known as one ofPterideophyte aquatic plants that can be utilized as fish feed for catfish because of its highnutritional values, including N, P, Si, Ca, Fe, Mg, and some others. This study aims to analyzethe effectiveness of feeding Azolla Microphylla on catfish length and weight growth by anexperimental method. A completely randomized design was conducted with 5 treatments and 4repeatabilities using 20 fish farms containing a cluster of catfish with an average size of 5 cm,that regularly fed with Azolla Microphylla. The observation was conducted every 10 daysduring the treatment, with a total number of observations held 4 times in the 40-daystreatment. The result indicated that the treatment in P2, with a 60-gram dosage of AzollaMicrophylla feeding, gives the optimal growth on catfish length and weight compared to othertreatments. Best scores in P2 treatment is found in the fourth observation, where the catfishlength reaches around 28 cm, and the weight reached 100 gram. Based on the single factorANOVA test, the real difference values for each group and treatment which analysed at asignificance level of 0,05, namely FvaluesFtable, indicates a significant effect of AzollaMicrophylla on the catfish growth. The Tukeyâ€™s Honest Significant Difference test also showsa significant effect of the Azolla Microphylla feeding on the catfish length and weight growth.Therefore, feeding catfish with 60-gram of Azolla Microphylla creates an effective treatmentto gain catfish length and weight.Keywords: Azolla Microphylla, Feeding, Fish Feed, Catfish GrowthÂ